Effects of pilates practice on postural changes: a narrative review (Research, Society and Development, 2022)
Objective: to understand the effects that the practice of Pilates promotes on postural changes. Materials and Methods: data collection took place between June and October 2022 through the scientific databases PubMed, LILACS (Latin American and Caribbean Literature on Health Sciences), VHL (Virtual Health Library) and Scielo. Associated with this, the following Boolean descriptors and operators will be used: Pilates AND bad posture, pilates AND low back pain, pilates AND students. Results: the Pilates method can be practiced by all age groups because it is a method that aims at the individual need of each one and has a wide prescription to reduce the discomforts of the lumbar region. It is recommended for academics because it has the ability to promote body alignment, improve flexibility, correct muscle changes, strengthen the muscles that help in posture and thus ends up being preventive and rehabilitative. Pilates when planned and structured by the instructor, following the basic principles of the method, is effective in increasing the health and quality of life of practitioners. Thus, improving the functionality of the body, strengthening and stretching the musculature as a whole. Considerations Final: the Pilates method helps in physical capacity, body maintenance, improves skills and makes it possible to work the body in a global way, correcting posture, realigning the muscles and developing body stability, strength and balance.